The effect of filler content and chemical modifications on properties of coconut shell regenerated cellulose biocomposite films - Farah Norain Hahary (School of Materials Engineering, 2016)
This research study was focused on the investigation of tensile properties, crystallinity index, morphology and thermal properties of CS-RC biocomposite films. Tensile test performed to measure tensile strength, elongation at break and modulus of elasticity of composites. Meanwhile, Scanning electron microscopy (SEM) is an imaging technique used to observe the morphology or surface fracture properties of the CS-RC biocomposite films. Thermal properties of biocomposites films were studied by using thermogravimetic analysis (TGA). Besides that, Fourier Transform Infrared Spectroscopy (FTIR) was used to investigate the functional group of CS-RC biocomposite films. Crystallinity index (CrI) was studied by using X-Ray diffraction (XRD).